Social media sentiment analysis to monitor the performance of vaccination coverage during the early phase of the national COVID-19 vaccine rollout. (June 2022) - Rahmanti, Annisa Ristya; Chien, Chia-Hui; Nursetyo, Aldilas Achmad; Husnayain, Atina; Wiratama, Bayu Satria; Fuad, Anis; Yang, Hsuan-Chia; Li, Yu-Chuan Jack
Highlights: Social media enables real-time monitoring of public sentiments to the government risk messages. The government can speed up its vaccination rate by analyzing the dynamics of netizens' tweets. Social media sentiment analysis can reinforce individual willingness to get vaccinated. Public sentiment on the COVID-19 vaccine is correlated with the increase of vaccination coverage. COVID-19 vaccine sentiment trend gradually changes to positive with the growth of trust emotion. Abstract: Background and objective: Social media sentiment analysis based on Twitter data can facilitate real-time monitoring of COVID-19 vaccine-related concerns. Thus, the governments can adopt proactive measures to address misinformation and inappropriate behaviors surrounding the COVID-19 vaccine, threatening the success of the national vaccination campaign. This study aims to identify the correlation between COVID-19 vaccine sentiments expressed on Twitter and COVID-19 vaccination coverage, case increase, and case fatality rate in Indonesia. Methods: We retrieved COVID-19 vaccine-related tweets collected from Indonesian Twitter users between October 15, 2020, to April 12, 2021, using Drone Emprit Academic (DEA) platform. We collected the daily trend of COVID-19 vaccine coverage and the rate of case increase and case fatality from the Ministry of Health (MoH) official website and the KawalCOVID19 database, respectively. We identified the public sentiments, emotions, word usage, and trend of all filtered tweets 90 days before and after the national vaccination rollout in Indonesia. Results: Using a total of 555, 892 COVID-19 vaccine-related tweets, we observed the negative sentiments outnumbered positive sentiments for 59 days (65.50%), with the predominant emotion of anticipation among 90 days of the beginning of the study period. However, after the vaccination rollout, the positive sentiments outnumbered negative sentiments for 56 days (62.20%) with the growth of trust emotion, which is consistent with the positive appeals of the recent news about COVID-19 vaccine safety and the government's proactive risk communication. In addition, there was a statistically significant trend of vaccination sentiment scores, which strongly correlated with the increase of vaccination coverage (r = 0.71, P <.0001 both first and second doses) and the decreasing of case increase rate (r = -0.70, P <.0001) and case fatality rate (r = -0.74, P <.0001). Conclusions: Our results highlight the utility of social media sentiment analysis as government communication strategies to build public trust, affecting individual willingness to get vaccinated. This finding will be useful for countries to identify and develop strategies for speed up the vaccination rate by monitoring the dynamic netizens' reactions and expression in social media, especially Twitter, using sentiment analysis.